Environmental Impact Assessment of the Eyvashan Dam using the Leopold modified matrix and Rapid Impact Assessment Matrix (RIAM) - mehdi komasi; behrang beiranvand (Mashhad University of Medical Sciences, 2019)
Abstract Background and Aim: Major Dam construction projects have increased due to widespread climate change, as a result of increased drought, human population growth and, consequently, increased global demand for energy and water. However, without comprehensive research, a large project such as a dam will have many irreversible and unpredictable effects on the environment. In this paper, the environmental impacts of Eyvashan dam in two phases of construction and exploitation on biological, physical-chemical, economic-social, cultural and strategic environments have been identified and studied. Materials and Methods: In the study of the environmental impact assessment of the Eyvashan dam with regard to development and evolution, as well as the abundant use of matrices in construction projects, the modified Leopold matrix method and the rapid impact assessment matrix have been used. The field survey and questionnaire were used to evaluate the construction and operation activities on the environmental components. Results: The results showed that the most negative effects in both construction and utilization phases were in both Leopold modified matrix and the rapid impact assessment matrix related to the physical-chemical environment and the most positive effects of the socio-economic environment for both phases. Conclusion: By comparing the many positive effects of construction and exploitation of the dam in terms of socio-economic status, the construction of the dam can be considered as an appropriate alternative to the physical-chemical negative effects. Also, in the results of both matrices, there was a very suitable adaptation matrix that can confirm the accuracy of the results in the environmental assessment of the Eyvashan dam in two stages of construction and operation.